Academic competition-based learning cultivates scientific literacy to promote professional competitiveness in medical undergraduates - Ruan, Yan; Zhang, Junlei; Wang, Jiali; Jian, Rui; Mei, Feng; Li, Hongli; Zhang, Yun; Hu, Qiwen; Xiao, Lan; Yang, Yi; Li, Ming; Xiong, Jiaxiang; et al. (Frontiers in Public Health, 2025)
BackgroundContemporary healthcare requires medical professionals with advanced scientific literacy. Current undergraduate medical curricula may not consistently develop this critical skillset. This study evaluates the effectiveness and challenges of an academic competition-based learning (ACBL) for enhancing scientific literacy in medical undergraduates.MethodsThe International Genetically Engineered Machine (iGEM) Competition based program was developed using a two-round modified Delphi study. 30 students participated in an iGEM-based academic competition during 18 months. Scientific literacy domains were assessed through validated questionnaires during a five-year follow-up period.ResultsiGEM participants demonstrated significantly greater improvement in literature review, experimental design, technical execution, presentation skills, and research management compared to controls (p < 0.01). Significant gains were observed in scientific knowledge acquisition and scientific reasoning (p < 0.01). Scores for active learning, critical thinking, and collaborative communication were significantly higher in the iGEM group (p < 0.05). Participants identified laboratory resources, space, equipment and funding as primary implementation constraints.ConclusionACBL is an innovative and effective strategies to develop students’ scientific literacy for professional competitiveness, which highlights the potential of ACBL as a transformative approach in medical education.